Pengaruh ROA, DAR dan NPM Terhadap Harga Saham Perusahaan: Studi Empiris pada Perusahaan Manufaktur Sub-Sektor Kosmetik dan Barang Keperluan Rumah Tangga yang terdaftar di Bursa Efek Indonesia (BEI) pada Tahun 2018-2022 - Siahaan, Johan Putra Octavian; Lumban Gaol, Herawati Feronika; Sinaga, Averia; Tampubolon, Serenova Elizabeth; Siallagan, Hamonangan; Sipayung, Rizki Christian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aims of this research is to determine the effect of ROA, DAR and NPM on stock prices. The population of this research are manufacturing companies in the Cosmetics and Household sub-sector which are listed on the Indonesia Stock Exchange (BEI) in 2018-2022. Purposive sampling appliied as the sampling method, and according to the established criteria, there were fives companies that met the criterias to be sampled. Quantitative methods with multiple linear regression analysis tools applied in this research. This research showed that Return On Assets (ROA) partially had a positive and significant effect on stock prices. Meanwhile, the Debt to Assets Ratio (DAR) and Net Profit Margin (NPM) partially have a negative and insignificant effect on stock prices. The Coefficient of Determination value (R2) is 0.566 which indicates that stock price as a variable Y is influenced by Return On Assets (X1), Debt to Asset Ratio (X2), and Net Profit Margin (X3) of 56.6%, while the other 43.4% is influenced by other variables outside the variables studied. Keywords: Return on Assets, Debt to Assets Ratio, Net Profit Margin, Stock Prices, Cosmetics & Household.